Influence of postoperative low-level laser therapy on the osseointegration of self-tapping implants in the posterior maxilla: A 6-week split-mouth clinical study - Mandić, Borka; Lazić, Zoran; Marković, Aleksa; Mandić, Bojan; Mandić, Miška; Djinić, Ana; Miličić, Bojana (Vojnosanitetski pregled, 2015)
Background/Aim. Low-level laser therapy (LLLT) has been proven to stimulate bone repair, affecting cellular proliferation, differentiation and adhesion, and has shown a potential to reduce the healing time following implant placement. The aim of this clinical study was to investigate the influence of postoperative LLLT osseointegration and early success of self-tapping implants placed into low-density bone. Methods. Following the split-mouth design, self-tapping implants (n = 44) were inserted in the posterior maxilla of 12 patients. One jaw side randomly received LLLT (test group), while the other side was placebo (control group). For LLLT, a 637 nm gallium-aluminum-arsenide (GaAlAs) laser (Medicolaser 637, Technoline, Belgrade, Serbia) with an output power of 40 mW and continuous wave was used. Low-level laser treatment was performed immediately after the surgery and then repeated every day in the following 7 days. The total irradiation dose per treatment was 6.26 J/cm² per implant. The study outcomes were: implant stability, alkaline-phosphatase (ALP) activity and early implant success rate. The follow-up took 6 weeks. Results. Irradiated implants achieved a higher stability compared with controls during the entire follow-up and the difference reached significance in the 5th postoperative week (paired t-test, p = 0.030). The difference in ALP activity between the groups was insignificant in any observation point (paired t-test, p > 0.05). The early implant success rate was 100%, regardless of LLLT usage. Conclusion. LLLT applied daily during the first postoperative week expressed no significant influence on the osseointegration of self-tapping implants placed into low density bone of the posterior maxilla. Placement of self-tapping macro-designed implants into low density bone could be a predictable therapeutic procedure with a high early success rate regardless of LLLT usage.
Keywords: dental implants; oral surgical procedures; laser therapy; low-level; bone regeneration; alkaline phosphatase; treatment outcome